Hydropneumatic Suspension Systems - Bauer, Wolfgang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2022)
Hydropneumatic suspension systems combine the excellent properties of gas springs with the favourable damping properties of hydraulic fluids. The advantages of these systems are particularly appropriate for mobile applications, such as agricultural and construction equipment as well as passenger cars, trucks and busses. Based on his 20 years of experience with this technology, Dr. Bauer provides in this book an extensive overview of hydropneumatic suspension systems. Starting with a comparison of different types of suspension systems, the author subsequently describes the theoretical background associated with spring and damping characteristics of hydropneumatic systems. Furthermore, he explains the design of the most important system components and gives an overview of level control systems, various special functions, patents and design examples. Finally, an outlook for future hydropneumatic suspension systems is discussed. Compared to the first edition, this new edition puts an additional focus on damping functions as well as applications / projects and contains various additional details such as proportional valves, all-wheel suspension or dediated power supply. Furthermore, suspension testing has been added as a new chapter.
Preface -- Suspension systems basics -- Spring and damping characteristics of hydropneumatic suspension systems -- Dimensioning of the hydropneumatic suspension hardware -- Hydraulic components design -- Level control -- Special functions of hydropneumatic suspension systems -- Suspension testing -- Design examples -- Important patents -- Looking into the future -- Index of symbols and abbreviations -- References -- Index.
Keywords: Automotive engineering; Multibody systems; Vibration; Mechanics, Applied; Automotive Engineering; Multibody Systems and Mechanical Vibrations; Automobiles -- Springs and suspension